Tantangan Strategis dan Strategi Optimalisasi untuk Pengembangan Sumber Daya Manusia melalui Program Makan Bergizi Gratis di Indonesia - Fattur Shiddiq; Ghina Nabilah Effendi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study analyzes the strategic challenges and optimization pathways for human resource development through Indonesia’s Free Nutritious Meal Program (MBG), which is aligned with the national vision of Golden Indonesia 2045. The research addresses critical gaps stemming from persistent stunting rates (19.8%), heavy reliance on food imports (80% of milk needs), and ongoing public concerns over program transparency and accountability, despite a substantial budget allocation of IDR 71 trillion serving 19.47 million beneficiaries. Using a qualitative descriptive approach, the study integrates big data from social media, online news, and academic publications. The analysis uses NVivo 15 Plus software to explore word frequency, sentiment polarity, and thematic factor categorization related to MBG implementation. Results reveal key challenges such as infrastructure limitations, import dependency, perceived corruption risks, and predominantly neutral public sentiment. To optimize outcomes, the study recommends three strategic directions: (1) enhancing national food self-sufficiency, (2) establishing Nutrition Food Processing Centers (Sentra Pengolahan Pangan Gizi, SPPG) across all regions, and (3) recruiting Indonesian Development Driving Graduates (Sarjana Penggerak Pembangunan Indonesia, SPPI) to ensure professional program management and policy compliance. The MBG initiative represents a transformative step in reshaping Indonesia’s nutrition and education landscape, catalyzing the development of competitive, high-quality human capital essential for achieving Indonesia’s long-term socio-economic vision.